HIPEC application potential in the treatment of extensive carcinomatosis in ovarian cancer (retrospective study) - S. I. Radostev; L. A. Kolomiets; A. V. Shelekhov; R. A. Zubkov; D. D. Morikov; А. A. Medvednikov (Acta Biomedica Scientifica, 2024)
Background. The high prevalence of advanced forms of cancer currently requires new treatment approaches. Only modern high-tech surgical procedures can provide means for improving the results of treatment.The aim. To study the results of treatment of patients with ovarian cancer with symptoms of peritoneal carcinomatosis using the HIPEC (Hyperthermic IntraPEritoneal Chemotherapy) method.Materials and methods. The study was conducted in Irkutsk Regional Cancer Center and included 88 patients. They were divided into 2 groups: group 1 – primary cytoreductive surgery (CRS) with the HIPEC method (41 patients); group 2 – primary cytoreductive surgery (47 patients). The most important criterion was the peritoneal cancer index (PCI). If the PCI was ≤ 14, we chose cytoreductive surgery with or without HIPEC.Results. PCI analysis showed differences in its values between the study groups (CRS – 10.17 ± 0.952; CRS + HIPEC – 12.93 ± 0.744; p = 0.002). There was an increase in length of stay in patients who underwent major surgeries in combination with HIPEC (21.8 ± 0.9 days versus 14.5 ± 0.6 days in the CRS group; p = 0.001). The CRS + HIPEC group had a longer duration of surgery (394.88 ± 19.935 min vs. 172.98 ± 11.514 min in the CRS group; p = 0.001). There was an increase in the overall percentage of postoperative complications in the CRS + HIPEC group – up to 26.8 % without statistically significant differences with the CRS group – 8.5 % (p = 0.082). The median time of relapse onset in the CRS + HIPEC group was 26 ± 4.3 months, while in the CRS group it was 18 ± 2.6 months.Conclusion. Using HIPEC method has proven its significance in increasing diseasefree survival.